2019
DOI: 10.1186/s13033-019-0295-6
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of domestic violence prevention and control in Vietnam from 2003 to 2018: a case study of policy development and implementation within the health system

Abstract: Background: Internationally, mental health and social care systems face significant challenges when implementing policy to prevent and respond to domestic violence (DV). This paper reviews the policy process pertaining to the national law on domestic violence prevention and control (DVPC) within the health system in Vietnam from 2003 to 2018, and critically examines the policy-making process and content, the involvement of key actors and the barriers to implementation within the health system. Methods: 63 poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…IPV has become a topic of national concern in Vietnam [36]. However, certain policies tend to increase gender-related violence towards women [37] despite the adoption of recent laws in favor of gender equity and against violence towards women [38]. As a consequence, underlying gender and power imbalances lead to IPV [39], and women have little "possibility to make independent decisions about their own reproductive health" in rural areas [40].…”
Section: Discussionmentioning
confidence: 99%
“…IPV has become a topic of national concern in Vietnam [36]. However, certain policies tend to increase gender-related violence towards women [37] despite the adoption of recent laws in favor of gender equity and against violence towards women [38]. As a consequence, underlying gender and power imbalances lead to IPV [39], and women have little "possibility to make independent decisions about their own reproductive health" in rural areas [40].…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the management of sexual violence against children in almost all health facilities. Some studies have shown that although health sector nancing is decentralised from state funds, the health sector did not plan a speci c budget allocated to DV-related activities [41].…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the management of sexual violence against children in almost all health facilities. Some studies have shown that although health sector financing is decentralised from state funds, the health sector did not plan a specific budget allocated to DV-related activities [34].…”
Section: Documents Alignment With National Policiesmentioning
confidence: 99%